Multislice CT angiography as a roadmap for pedicle selection prior to breast reduction surgery - Noura Yousef Zakhary; Amr Ahmed Mubarak; Osama Helmy Elkhadrawy; Elsayed Mandour Ismail (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Accurate knowledge of breast arterial supply on individual basis is crucial prior to breast reduction surgery to minimize the risk of post-operative necrosis of nipple-areola complex which is a well reported complication. The purpose of this cross-sectional study was to test the ability of multislice CT angiography to delineate the dominant arterial supply of nipple-areola complex to facilitate accurate breast pedicle selection to improve patient outcome. Results Twelve patients underwent multislice CTA of both breasts to delineate dominant arterial supply to NAC, internal mammary artery was the dominant arterial supply in most of breasts (87.5%) based on CTA findings and hence superomedial pedicle was the commonest pedicel chosen. None of patients experienced NAC necrosis postoperatively while minority of patients (16.6%) exhibited decreased NAC sensation bilaterally. Conclusions Multislice CT angiography is a useful pre-operative tool to minimize the risk of post-operative necrosis of nipple-areola complex in patients undergoing breast reduction surgery.